Adaptation and Psychometric Properties of an Instrument to Assess Self-Efficacy in Client-Centeredness (SECCQ). - Gerdts-Andresen, Tina; Glømmen, Anne Margrethe; Hjelmeland, Inger; Haug, Erna; Grønlien, Heidi K. (Journal of Social Work Education)
This article assesses the reliability and validity of the Self-Efficacy in Client-Centredness questionnaire (SECCQ). SECCQ assesses social worker students' subjective belief in their ability to provide client-centered care in their daily interaction with children or families. Self-efficacy is defined as an individual's judgments concerning their capability to perform certain skills necessary to attain a desired outcome of behavior. Client-centeredness, on the other hand, relates to how social workers treat clients, not only from a clinical perspective, but also from an emotional, mental, and social perspective. Overall findings demonstrate that this questionnaire has satisfying psychometric properties and high reliability. Hence, the SECCQ may be a valuable tool for raising students' awareness of their self-efficacy and the evaluation of student learning outcomes.